Occurrence of Acanthosis Nigricans, A Benign Condition or Associated with Systemic Disease. A Case-Control Study - R. Acharya; A. Rijal (Nepal Journal of Dermatology, Venereology & Leprology)
Background: Acanthosis nigricans (AN), a common cutaneous finding, characterized by hyperpigmentation and velvety hyperplasia of the epidermis affecting flexures. Its exact prevalence varies according to age, race, degree of obesity and endocrinopathy.